Fabrication of a mercaptoacetic acid pillar[5]arene assembled nanochannel: a biomimetic gate for mercury poisoning. Issue 5 (11th February 2016) - Zhang, Fan; Ma, Junkai; Sun, Yue; Boussouar, Imene; Tian, Demei; Li, Haibing; Jiang, Lei
Abstract : Herein, based on biomimetic strategies, a tunable mercury(ii ) ion-gate modulated by mercaptoacetic acid-pillar[5]arene (MAP5 ) is reported. Abstract : Mercury ion binding blocks potassium ion channels, which leads to toxicity in vivo . It is challenging to design a simple and efficient artificial system to mimic the sophisticated biological process of mercury poisoning. Herein, based on biomimetic strategies, a tunable mercury(ii ) ion-gate modulated by mercaptoacetic acid-pillar[5]arene (MAP5 ) is reported. By virtue of the unique design of the host–guest competition, potassium ion transport can actualize the reversible switching between "on" and "off" in the absence and presence of mercury ions. Moreover, theMAP5 -immobilized nanochannel is highly effective at distinguishing Hg 2+ from other metal ions and can be used to detect Hg 2+ and act as an excellent and robust gate valve for developing integrated circuits and nanoelectronic logic devices. This study paves a new way for better understanding the physiological phenomenon of mercury toxicity and shows great promise for biomedical research.